Uncertain Futures: Understanding Work and Retirement Inequalities facing Women Over 50 in Manchester, UK - Campbell, Sarah; James, Hayley; Dewhurst, Elaine (Magyar Gerontológia, 2024)
This paper will explore data generated through a coproduced art research project called Uncertain Futures. The project set out to explore the inequalities facing women over 50 in relation to work in Manchester, UK.